1995
DOI: 10.1161/01.cir.92.6.1558
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Ventricular Induction of Brain Natriuretic Peptide Gene Expression in Experimental Acute Myocardial Infarction

Abstract: These results demonstrate the rapid induction of ventricular BNP gene expression in rats with AMI compared with ANP and suggest that BNP gene expression in the ventricle is regulated distinctively from ANP gene expression against acute ventricular overload. They also suggest that the BNP gene can be one of the acutely responsive cardiac genes for the ventricular overload and suggest a possible pathophysiological role of BNP distinct from ANP in AMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
195
1
14

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 390 publications
(224 citation statements)
references
References 38 publications
14
195
1
14
Order By: Relevance
“…This paradigm has been previously demonstrated for GC-A signaling via a rapid activation/release of cardiac natriuretic peptides (ANP and B-type natriuretic peptide) after acute myocardial infarction. 41,42 Regardless, the molecular mechanisms underlying the regulation of GC-G under I/R require further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…This paradigm has been previously demonstrated for GC-A signaling via a rapid activation/release of cardiac natriuretic peptides (ANP and B-type natriuretic peptide) after acute myocardial infarction. 41,42 Regardless, the molecular mechanisms underlying the regulation of GC-G under I/R require further elucidation.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the size of infarct was in fact proportional to the level of NT-proBNP in a high-risk population with a larger extent of muscle at risk for necrosis. Mechanistically, this may relate to the release of presynthesized BNP from necrosing areas, an increase in messenger RNA in peri-infarct myocytes or increased wall stress in the remaining viable peri-infarct myocardium (21). Although no conclusive evidence exists, elevated NT-proBNP may indicate that there is more viable myocardium surrounding the infarct zone, and this elevation in NT-proBNP may portend an increased risk of adverse outcome because the peri-infarct zones are more likely to produce a lethal arrhythmia than noninfarcted tissue or scar tissue.…”
Section: Size Of Infarctmentioning
confidence: 99%
“…Thus, it takes several hours for the plasma natriuretic peptide levels to increase significantly after the onset of acute myocardial stretch. 15 This process includes myocardial BNP messenger ribonucleic acid (mRNA) synthesis, prohormone synthesis, and prohormone release into the circulation (Figure 1). Similar to cardiac troponins, elevations in BNP and NTproBNP are associated with right ventricular dysfunction in acute PE.…”
Section: Natriuretic Peptidesmentioning
confidence: 99%